Removal of 1-Butanethiol from Diesel Oil by Red Mud - Singh A.P.; Singh P.C.; Singh V.N. (My University, 2025)
The use of red mud for removal of 1-butanethiol from diesel oil at different concentrations and temperatures has been investigated. Low concentration and high temperature favor the percentage removal of 1-butanethiol from diesel oil. The process follows a first-order adsorption rate expression and is controlled by intraparticle transport. Equilibrium data at different temperatures follow the Langmuir mode of adsorption. Thermodynamic parameters for the present system indicate spontaneous and endothermic natures of adsorption with positive entropy change. © 1988, American Chemical Society. All rights reserved.